Soy, red clover, and isoflavones and breast cancer: a systematic review. - Heidi Fritz; Dugald Seely; Gillian Flower; Becky Skidmore; Rochelle Fernandes; Sarah Vadeboncoeur; Deborah Kennedy; Kieran Cooley; Raimond Wong; Stephen Sagar; Elham Sabri; Dean Fergusson (PLoS ONE)
Background Soy and red clover isoflavones are controversial due to purported estrogenic activity and possible effects on breast cancer. We conducted a systematic review of soy and red clover for efficacy in improving menopausal symptoms in women with breast cancer, and for potential impact on risk of breast cancer incidence or recurrence. Methods We searched MEDLINE, Embase, the Cochrane Library, and AMED from inception to March 2013 for human interventional or observational data pertaining to the safety and efficacy of soy and red clover isoflavones in patients with or at risk of breast cancer. Results Of 4179 records, we included a total of 131 articles: 40 RCTs, 11 uncontrolled trials, and 80 observational studies. Five RCTs reported on the efficacy of soy for hot flashes, showing no significant reductions in hot flashes compared to placebo. There is lack of evidence showing harm from use of soy with respect to risk of breast cancer or recurrence, based on long term observational data. Soy intake consistent with that of a traditional Japanese diet (2-3 servings daily, containing 25-50mg isoflavones) may be protective against breast cancer and recurrence. Human trials show that soy does not increase circulating estradiol or affect estrogen-responsive target tissues. Prospective data of soy use in women taking tamoxifen does not indicate increased risk of recurrence. Evidence on red clover is limited, however existing studies suggest that it may not possess breast cancer-promoting effects. Conclusion Soy consumption may be associated with reduced risk of breast cancer incidence, recurrence, and mortality. Soy does not have estrogenic effects in humans. Soy intake consistent with a traditional Japanese diet appears safe for breast cancer survivors. While there is no clear evidence of harm, better evidence confirming safety is required before use of high dose (≥ 100 mg) isoflavones can be recommended for breast cancer patients.